Optimizing Post-Training Recovery in Student Futsal: The Effects of Sport Massage and Relaxation on VO2Max - Hasani, Muh. Hibatilla; Muhaimin, Ali; Muhsan, Muhsan; Irmansyah, Johan; Kurnianto, Haris (Sportify Journal, 2025)
This study was motivated by the low endurance of several futsal extracurricular participants, indicated by rapid fatigue, muscle cramps, body soreness, and the absence of a systematic post-training recovery program. The study aimed to examine the effects of sport massage, relaxation, and combined sport massage with relaxation on the stamina of futsal extracurricular students at MAN 1 Kota Bima. This research used a quantitative approach with a pretest-posttest design involving 24 participants. Stamina was measured using the bleep test to estimate VO2Max. Data were analyzed descriptively and inferentially through normality testing, paired samples t-test, and adjusted repeated-measures interpretation. The results showed that mean VO2Max increased from 41.5 to 47.4 after sport massage, 45.9 after relaxation, and 49.9 after the combined treatment. The study concludes that all recovery methods showed a tendency to improve stamina, with the combined treatment producing the highest descriptive result.